OP89 Challenges in Managing Multimorbid Patients: A Meta-Ethnography of the GPS Perspective. (10th September 2013) - Sinnott, C; Hugh, S Mc; Browne, J; Bradley, C P
Abstract : Background: Multimorbidity refers to the co-existence of two or more long-term conditions in an individual patient, and is the norm amongst patients attending primary care for chronic disease management. Qualitative research shows that GP's experience challenges in the management of patients with multimorbidity, which are not experienced in the management of single chronic diseases. However, it is unclear how the challenges revealed by individual studies relate to each other and the overall problem of managing multimorbidity. The aim of this study was to establish the overarching challenges faced by GPs in the management of multimorbid patients, by systematically reviewing and synthesising the published literature in this field. Methods: A systematic literature search and synthesis was performed using the meta-ethnographic approach described by Noblit and Hare. This 7 step model involves a process of comparison and cross-interpretation between studies but allows the context of the primary data to be preserved. Results: The initial search yielded 1805 potential papers. Following screening, 10 papers were included in the review. Four overarching concepts emerged from these papers: 1) Organisation & Fragmentation of Health Care, 2) Conflict with evidence based medicine 3) Delivering patient centred care 4) Challenges in Shared Decision Making. Subthemes developed within the core concepts, and many cases of contradictory opinions were seen. By translating individual studies to the key concepts higher order interpretations were developed and a 'line of argument' was drawn. The line of argument pointed to GP's sense of isolation in decision making for patients with multimorbidity. Discussion: This systematic review and qualitative synthesis has generated a fuller understanding of the difficulties in managing multimorbidity than would be possible from a single study. It has generated novel findings, most strikingly that GPs feel professionally isolated when making decisions for multimorbid patients. Further research is required to explore the reasons for this in order to design interventions that may help GPs in this regard.